Transition-Metal-Catalyzed Synthesis of Spirolactones - Mostinski, Yelena; Lankri, David; Tsvelikhovsky, Dmitry (Synthesis, 2017)
Spiranoid lactone structures can frequently be observed as scaffold segments of various biochemical compounds and drugs of natural origin. Examples of these structures have been identified among terpenoids, alkaloids, steroids, carbohydrates, and many other natural products. Such a broad natural diversity and biological activity allows a wide spectrum of these systems to be attractive targets for synthetic and medicinal chemists. Covering a broad spectrum of recognized approaches toward the design of spirolactones established over the past several decades, this review focuses on transition-metal-catalyzed synthesis, which is the most prominent methodology reported to date.1 Introduction2 Patterned Approaches2.1 Cyclocarbonylation2.2 Hydroalkylation/Arylation of Hydroxy α,β-Acetylenic Esters2.3 [2+2+2]-Cyclotrimerization: Rapid Access to Spirobenzofuranone Scaffolds2.4 Cyclization of Allenoic Acids/Allenoates2.5 Cycloisomerization–Oxidation of Homopropargyl Alcohols2.6 Hydroalkoxylation of Alkynoic or Alkenoic Acids2.7 C–H Carbonylation: Access to Spirobenzofuranone and Spiroisochromanone Derivatives2.8 Alkylative Spirolactonization of α,β-Unsaturated Esters2.9 Olefin Ring-Closing Metathesis2.10 Reductive Opening of Epoxides2.11 Intramolecular C–H Insertion3 Nonpatterned Approaches3.1 Azomethine Ylide Cycloaddition3.2 Hydrohydroxyalkylation of Vicinal Diols3.3 Photoredox Catalysis: C-Alkylation of Alcohols3.4 Carbonylative Spirolactonization of Hydroxycyclopropanols3.5 Copper-Catalyzed Alkylation of β-Keto Esters4 Conclusion
Keywords: spirolactones; cyclization; transition-metal catalysis; lactonization